Assessment of prescribing patterns of physicians on the treatment of community-acquired pneumonia (CAP) among immunocompetent adult patients in a level IV government hospital - Co, Krizia Joy A.
Community-acquired pneumonia (CAP) has been a global health concern for years, being responsible for an estimated five millions deaths annually. In the Philippines, there are more than 40.000 cases of CAP also rank as the 1st leading cause of morbidity from 2001 to 2005, and the 5th leading cause of mortality in 2006. The 2010 Philippine Practice Guideline (PCPG) categories CAP as low-risk (LR), moderate-risk (MR) and high-risk (HR).This study sought to evaluate the drug prescribing patterns and associated drug costs in the treatment of CAP-LR and CAP-MR among immunocompetent adult patients in a level IV government hospital . A descriptive analysis using review of records was performed for patient medical records between July 2011 to June 2012.Results revealed low compliance to the PCPG among the physicians.12.5% for CAP-LR and 44% for CAP-MR. Examples of non-compliance identified were prescription of a drug not recommended for the CAP classification, prescription of a drug not included in the PCPG, and prescription of a frequency different from the recommended. This poor compliance to the PCPG resulted to an excess drug cost of P41.11 for low-risk CAP patients and additional cost ranging from P437.09 to P2,722 for moderate-risk CAP patients. Treatment guidelines are in place to provide a cost-effective treatment, reduce incidence of adverse events, prevent bacterial resistance and avoid failure of treatment. Understanding factors associated with poor compliance to these guidelines may be explored so these could be properly addressed and strategic efforts may be created to increase compliance to existing treatment guidelines.